1999
DOI: 10.1073/pnas.96.19.10620
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein phosphatase 2A induces serine/threonine phosphorylation, subcellular redistribution, and functional inhibition of STAT3

Abstract: Signal transducers and activators of transcription (STATs) are rapidly phosphorylated on tyrosine residues in response to cytokine and growth factor stimulation of cell surface receptors. STATs hereafter are translocated to the nucleus where they act as transcription factors. Recent reports suggest that serine phosphorylation of STATs also is involved in the regulation of STAT-mediated gene transcription. Here, we studied the role of serine͞threonine phosphatases in STAT3 signaling in human antigen-specific CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
102
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 39 publications
9
102
1
Order By: Relevance
“…22,23 In brief, cells (1 Â 10 6 ) were incubated for 12 h (SOCS3wt) or 24 h (STAT3wt and STAT3D) with 20 ng/ml Tetracycline (Tet) (Invitrogen, Taastrup, Denmark). Cells were then pelleted, lysed in ice-cold lysis buffer, and subjected to Western blotting using the indicated antibodies.…”
Section: Protein Extraction and Western Blottingmentioning
confidence: 99%
“…22,23 In brief, cells (1 Â 10 6 ) were incubated for 12 h (SOCS3wt) or 24 h (STAT3wt and STAT3D) with 20 ng/ml Tetracycline (Tet) (Invitrogen, Taastrup, Denmark). Cells were then pelleted, lysed in ice-cold lysis buffer, and subjected to Western blotting using the indicated antibodies.…”
Section: Protein Extraction and Western Blottingmentioning
confidence: 99%
“…22,26 Myc-Tagged SOCS-3 was immunoprecipitated using 5 mg anti-Myc (9E10) (Santa Cruz Biotechnology, Santa Cruz, CA, USA) and Protein-A agarose beads (KemEn-Tec, Copenhagen, Denmark). Membranes were probed using antibodies specific for Myc (9E10), Anti-Stat1, anti-Stat6, and anti-SOCS-3 from Santa Cruz, anti-PY-Stat1 and anti-PY-Stat5 from New England Biolabs (Beverly, MA, USA), anti-PY-Stat3 from Nanotools (Denzlingen, Germany), anti-Stat3 and antiStat5 from Transduction Laboratories (Lexington, KY, USA), antiPhosphor-tyrosine (PY) 4G10 from Upstate Biotechnologies, and HRP-conjugated anti-rabbit Ig, HRP-conjugated anti-mouse Ig, or HRP-conjugated anti-goat Ig from Dako (Glostrup, Denmark) and evaluated using enhanced chemiluminescence (ECL) according to the manufacturers instructions (Amersham, Buckinghamshire, UK).…”
Section: Western Blotting and Antibodiesmentioning
confidence: 99%
“…There is general agreement that phosphorylation of Stat1 and Stat3 on serine 727 enhances the transcriptional potency of tyrosinephosphorylated Stat dimers (46,61,74,76,78,79), and one study suggests that DNA binding is enhanced as well (72). However, several studies have suggested that serine phosphorylation of Stats actually suppresses tyrosine phosphorylation and DNA binding (58,60,66,80), although only one of these studies tested this directly using a mutated Stat (58). We have not excluded that serine phosphorylation of Stats may contribute to modulating Stat activity in our system, but several lines of evidence suggest that the predominant site of inhibition occurs upstream of Stats.…”
Section: Figurementioning
confidence: 99%